Prospective associations between physical activity levels and white matter integrity in older adults: results from the MAPT study. (July 2020) - Maltais, Mathieu; Rolland, Yves; Boisvert-Vigneault, Katherine; Perus, Lisa; Mangin, Jean-François; Grigis, Antoine; Chupin, Marie; Bouyahia, Ali; Gabelle, Audrey; Delrieux, Julien; Vellas, Bruno; de Souto Barreto, Philipe
Highlights: This is the longest study looking at physical activity levels and brain health. The condition of the uncinate fasciculus region is associated with levels of physical activity. High levels of physical activity may be beneficial in preventing a decline in the integrity of the fronto-temporal region. Abstract: Background: Higher levels of physical activity (PA) are known to be associated with better white matter integrity measured by diffusion tensor imaging (DTI) in older adults in cross-sectional studies. However, no studies have investigated the association between PA levels and the evolution of DTI parameters (fractional anisotropy and mean diffusivity). Objectives: To examine the cross-sectional associations between PA levels and DTI parameters, then to investigate the association between baseline PA levels and the evolution of DTI parameters in older adults. Methods: Data on magnetic resonance imaging with DTI method from the Multidomain Alzheimer's Preventive Trial (MAPT) study were used; 228 participants had data on DTI measured at three time-points over five years. Fractional anisotropy and mean diffusivity were acquired for six different brain regions. Results: No significant associations were found in the cross-sectional analyses. Only one association was found: compared with active individuals, a faster worsening in the mean diffusivity of the uncinate fasciculus region was found in inactive individuals (-5.0 × 10 -6 (-9.5 × 10 -5, 4.9 × 10 -6 )). Conclusions: In this study, we found that the condition of the uncinate fasciculus region may be susceptible to changes in PA levels in older adults. Longitudinal studies that assess fitness and PA using objective measurements (e.g. cardiorespiratory fitness and accelerometry) could shed some new light on this topic.